DEVELOPING DESCRIPTIVE TEXT READING MATERIALS BASED ON CONSTRUCTIVISM APPROACH - Abdul Razak; Hermandra Hermandra; Elmustian Elmustian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research and development aimed to produce descriptive text reading materials based on constructivism approach. This research was conducted through the following procedures: 1) analyzing needs; 2) designing the product; 3) developing the initial product; 4) conducting a limited trial; 5) revising the product; 6) conducting a trial on a large scale; and 7) producting the product (a prototype). The instrument in this research was a questionnaire addressed to experts, users (Bahasa Indonesia teachers), and audience (students at grade VII SMP/MTs). Besides, a cloze test was also utilized to measure the readability of descriptive texts and the main narration of the learning materials. The development of the materials was carried out based on 5 phases constructivism by Needham. The product trial was carried out grade VII junior high schools in Kabupaten Lingga, Kepulauan Riau province which was not exposed to the Covid-19. This study concluded that the developed learning materials was feasible for reading descriptive text materials; it was expected that this materials provided a good contribution to the development of science in the field of education.